ÖSI och naturvården - Asplund, Brita (2019)
At the beginning of the 1970´s the Swedish forestry had developed into a highly mechanized and intensive operation. It received strong criticism for its methods and negative effects on the environment. However, when a new forest law was decided in 1979 environmental issues were not its main concern, but the production and supply of raw material for the forest industry.